Carbon emission equivalent of selected agroforestry systems in Zamboanga City, Philippines - Tabal, E. P.; Mendoza, T. C.; Paelmo, R. F.; Garcia, J. N. M.; Visco, R. G. (International Journal of Agricultural Technology, 2021)
The study was estimated the carbon emission equivalent expressed in tCO2e ha-1 derived from the individual energy inputs of the nine (9) major agroforestry systems (AFSs) identified across the 16 community-based forest management (CBFM) sites located mostly in the hilly and mountainous portion of Zamboanga City, Philippines. The energy input was calculated as direct energy input (DEI), indirect energy input (IEI) and embedded energy input (EEI) from the various cultural and management practices that falls on pre-land preparation, crop establishment, crop care and maintenance, harvest and postharvest operations. The total energy input (TEI) is the sum total of DEI, IEI and EEI computed in Mcal ha-1. All Mcal units were then converted into Liter Diesel Oil Equivalent (LDOE), where 1.0 LDOE = 11.414 Mcal = 3.96 kg CO2 equivalent emission LDOE-1. The total CO2 emission equivalent ranged from 2.01-4.09 tCO2e ha-1 across the 9 AFSs. Of this amount, the DEI, IEI and EEI contributed 1.6-5.4%, 94.1-98.0% and 0.35-0.53%, respectively. The high CO2 emission equivalent of IEI was attributed to high usage of external inputs such as inorganic fertilizers particularly N fertilizer, pesticides and labor. Other factors associated to high energy usage and its net carbon emission equivalent includes plant density and number of agricultural crop species present within an AFS. Understanding the significant contributions of various energy-intensive systems delineated into DEI, IEI and EEI will help policy makers and local planners to initiate a ‘green agriculture economy’ – a food production system with reduced energy and carbon footprints responsive to changing climate with higher economic potential for the upland growers in the City of Zamboanga, Philippines